Pola Interaksi Edukatif Guru dan Siswa dalam Menumbuhkan Motivasi Belajar Siswa Di MTs Al-Adawiyah Capar Kertek Wonosobo - Dini Syarifah; Maryono; Fatiatun (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study was motivated by the importance of educational interaction patterns between teachers and students in fostering learning motivation, especially in a boarding school-based madrasah environment with distinctive learning dynamics. This research focuses on describing the patterns of educational interaction between teachers and students, the teacher’s role in fostering students’ learning motivation, and the challenges faced in the interaction process at MTs Al-Adawiyah Capar, Kertek, Wonosobo. The study employed a descriptive qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. The findings show that the interaction pattern that developed was generally two-way, warm, and humanistic through the 5S culture, communicative approaches, and the teacher’s role as motivator, facilitator, and counselor. Students’ learning motivation increased when teachers provided attention, appreciation, and a safe space for communication. However, educational interaction still faced several obstacles, such as student boredom, monotonous teaching methods, limited learning media, and emotional instability. In conclusion, effective educational interaction plays an important role in building students’ learning motivation in a sustainable way.